Constraints and prospects of research capacity building for engineering undergraduates in Nigerian Universities (2012)
Research is an organizational study, which is concerned with methodical investigation into a subject in order to discover facts, to establish or revise a theory or to develop a plan of action based on the fact discovered. Universities, as centers of knowledge production and generation play a critical role in national research by maintaining research infrastructures and standards in all existing academic disciplines, creating new disciplines, and building research capacity through training of new researchers and influencing university teaching. Research capacity building is the process of enhancing the abilities of individuals, organizations and systems to undertake and disseminate high quality research efficiently and effectively. It involves improving research skills, as well as access to research information and resources. This study examines the constraints and prospects of building research capacity among engineering undergraduates of Nigerian universities. Based on the report of the last accreditation exercise of engineering departments across Nigerian universities, which showed that only 55% of engineering departments were fully accredited; the study identified the problem of low funding, poor curriculum design, lack of adequate industrial practice and the problem of staff qualification and experience as major constraints for effective research capacity building in the Nigerian engineering education sector. The study concluded by proposing a research capacity building framework for engineers that will assist in integrating research capacity building into the university engineering education curriculum in the country. The framework recommends improved funding of engineering departments, enhancement of university – industry relationship, renewed emphasis on industrial training, improved role of the accreditation bodies and changing of the licensing requirements for Nigerian engineers, as measures that will considerably improve the research capacity of engineering undergraduates.